PENGARUH HUBUNGAN PERTEMANAN DI INSTAGRAM TERHADAP KEBUTUHAN INTERPERSONAL REMAJA - Annisa Arifa (2021)
Everyone certainly has a relationship that is based on certain goals or needs, including friendship where in this era these relationships can be established through social media. For adolescent friendship is certainly very important in their social life, friendship is established because of the desire to be recognized in the group or the need for affection as a form of emotional support, the desired needs in a relationship are referred to as interpersonal needs. The purpose in this study was to find out how much influence friendships on Instagram had on the interpersonal needs of adolescent, 100 respondents became the object of research which is high school students in the East Jakarta area. The research methodologhy used is quantitative with explanative research type, using the Fundamental Interpersonal Relation Orientation (FIRO) theory as the basis for the assumptions. The results of this study indicate a significant correlation of r = 0.519 and the results of the coefficient of determination test are 36.5%, while the rest of could be involved by the other factors. Then, the results of the hypothesis test show that ho is rejected and ha is accepted, so there is a significant influence between friendship on instagram and adolescent interpersonal needs.